Karakteristik Fisiko-Kimia dan Mutu Sensoris Skin lotion Rumput Laut (Eucheuma cottonii) dengan Penambahan Kolagen Ikan Komersil - Rizky Rahmadhini Putri; Herpandi Herpandi; Rodiana Nopianti (Jurnal FishtecH, 2015)
The purposes of this research were to know the physicochemical characterirics and sensory quality of seaweed skin lotion (Eucheuma cottonii) by adding fish commercial collagen. This research used a factorial randomized block design (RAKF). Treatments this research were by combining of seaweed (0%, 2,5%, and 5%) and fish commercial collagen (0%, 2,5%, and 5%). The parameters in this research were the analysis of physical, chemical, and sensory. For sensory analysis using Friedmen test. The results of this research on pH and color parameters have a significant effect only when the addition of collagen with different concentrations, whereas the viscosity parameter and weight shrinkage give significant effect with addition on of seaweed and collagen with different concentrations. For pH values 6,50-7,41; viscocity 6000 cp – 9000 cp; whiteness 65,30%-76,77%; weight shrinkage 1,78%-5,95%; emulsion stability 100% and sensory assessment on all the attributes was ranged between kind of like to like by doing. The best treatment to the addition of seaweed 5% and collagen 5% (R2K2).